Teaching styles of teachers from different higher education careers associated with Natural Science - Julieta Laudadío; Claudia Mazzitelli (Pontificia Universidad Católica del Perú, 2015)
Teaching styles manifest the preferences in kind of teaching of professors, which involve certain teaching conceptions (Heimlich & Norland, 2002). Identification of teaching styles is the starting point to reflect on teaching practices and consistency between the theoretical and the practical way of teaching. The aim of this study is to identify the predominant teaching styles in professors who work in different higher level careers related with natural science and to analyze them in relation to career guidance. The results show the need of thinking about the characteristics of teachers training and about the importance of the integrationbetween disciplinary and pedagogical aspects.